Customer Satisfaction of Bank: A Comparative Study of Two Commercial Banks in Nepal - Regmi, Pawan; Gnawali, Dhruba (Curriculum Development Journal, 2025)
This study analyzes customer satisfaction within Nepal's banking sector, focusing on two, Rastriya Banijya Bank Limited (RBBL) and Nepal Investment Mega Bank Limited (NIMB). Using a mixed-methods approach combining SPSS-v28-analyzed financial metrics (loan/deposit growth, LDR from 2003-2024) and structured surveys of 200 customers, we connected satisfaction with financial performance. Results show RBBL led deposits (NPR 429.19B vs. NIMB’s NPR 403.41B in 2024), while NIMB dominated lending (NPR 319.74B vs. RBBL’s NPR 248.91B), reflecting post-merger growth. Critically, RBBL’s lower LDR (58.0%) indicates underutilized liquidity constraining innovation, while NIMB’s balanced LDR (79.2%) supports growth but risks service dilution. RBBL excels in branch accessibility (68% satisfaction) and remittances; NIMB leads digital adoption. Key drivers include service quality, digital platforms, and demographics. Recommendations: RBBL should deploy AI assisted rural kiosks and SME-focused products; NIMB requires dynamic pricing models and post-merger service standardization.